A review of transverse curvature effect on friction force and leading-edge flow. (15th December 2020) - Alam, Md. Mahbub
Abstract: The paper reviews the transverse curvature effect on the friction force on and the leading-edge flow around a cylinder subjected to axial flow. Skin friction coefficient ( C f ) on the cylinder surface could be predominant functions of Reynolds number ( Re a, based on cylinder radius a ), transverse curvature ( a +, normalized by friction velocity U τ ), and boundary-layer thickness ratio ( δ/a ). The relationships between C f, Re a, a +, and δ/a are analyzed, established, and presented in the form of empirical formulations. The C f at Re a  ≤ 2 × 10 3 is mainly dependent on δ/a while that at Re a  > 2 × 10 3 is largely contingent on Re a . The gaps of research into the axial flow cylinder are pointed out, namely, the literature lack the experimental study on large transverse curvature (small a + ). Graphical abstract: Image 1 Highlights: C f on the cylinder surface is predominant functions of Re a, a + and δ/a. The relationships between C f, Re a, a +, and δ/a are analyzed and established. The C f at Re a  ≤ 2 × 10 3 is mainly dependent on δ/a while that at Re a  > 2 × 10 3 is largely contingent on Re a .